PRENATAL YOGA UNTUK MENGURANGI KETIDAKNYAMANAN KEHAMILAN TRIMESTER 3 - Acholder Tahi Perdoman; Risqi Utami; Fitri Ramadhaniati (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2022)
In the process of adaptation to pregnancy, the mother often experiences discomfort. Physical and psychological changes make pregnant women feel tired quickly, have difficulty sleeping, short of breath, legs and arms edema. A study shows the prevalence of low back pain in pregnant women is still high, namely by 24% to 90%. A form of exercise that can help pregnant women feel comfortable during pregnancy or until the delivery process is prenatal yoga. This study aims to determine the effectiveness of prenatal yoga on reducing discomfort during pregnancy. The method used is a qualitative approach with the Literature Review Research method, which is carried out by browsing articles using Google Scholar, Garuda and other electronic media, using the keywords "Prenatal Yoga", "pregnant women", "inconvenience". Results obtained. Prenatal yoga can reduce discomfort in complaints of swelling in the legs, back pain, low back pain, leg cramps and difficulty sleeping. Prenatal yoga can be used as an alternative to midwifery care in overcoming the discomfort that occurs in pregnant women, especially in the third trimester. It is hoped that health workers, especially midwives, can provide information related to the benefits of prenatal yoga and can be a facilitator to do prenatal yoga